2013
DOI: 10.4103/0976-9668.116984
|View full text |Cite
|
Sign up to set email alerts
|

Ninety-one cases of ameloblastoma in an Indian population: A comprehensive review

Abstract: Aim:To assess the cases of ameloblastoma retrospectively for various parameters.Materials and Methods:Ninety-one previously reported cases of ameloblastoma from Government Dental College and Hospitals, Nagpur, were included in this study. Data were collected considering parameters such as age, sex, symptoms, radiographic, histopathology, treatment modalities, and recurrence. Our findings were also compared with world literature.Results:The average age was 32.5 years. Mostly men complained of an asymptomatic sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 18 publications
3
10
0
Order By: Relevance
“…They usually affect younger patients, with mean ages in the third decade of life, with predilection for the posterior mandible ( 17 ). The results of the present study showed that, contrarily to the literature ( 5 , 6 , 9 , 10 , 12 , 13 ) and similarly Hertog et al . ( 11 ), there was no statistically significant difference in the mean age of patients affected by solid and unicystic ameloblastomas; however, the few unicystic ameloblastomas included in the sample precludes any definite conclusion.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…They usually affect younger patients, with mean ages in the third decade of life, with predilection for the posterior mandible ( 17 ). The results of the present study showed that, contrarily to the literature ( 5 , 6 , 9 , 10 , 12 , 13 ) and similarly Hertog et al . ( 11 ), there was no statistically significant difference in the mean age of patients affected by solid and unicystic ameloblastomas; however, the few unicystic ameloblastomas included in the sample precludes any definite conclusion.…”
Section: Discussionsupporting
confidence: 80%
“…Ameloblastomas can produce extensive bone destruction but are mostly characterized by well-defined radiolucencies surrounded by cortical bone sclerosis, as demonstrated by the present results. Most studies reinforce the idea that ameloblastomas are mainly characterized by multilocular radiolucencies, especially the solid subtype ( 6 , 7 , 12 , 13 ), but some have demonstrated an equal distribution or even predominance of unilocular radiolucencies ( 3 , 5 , 10 ). In the present study, mean greatest diameter of the tumors was 46 mm and, due to large size of some tumors, symptoms such as pain and discharge were found in one third of the cases, similarly to other studies ( 5 - 7 , 13 ).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Ameloblastoma is a benign epithelial odontogenic tumor with two quite different intraosseous biologic variants [ 52 ]. The multicystic ameloblastoma (MA) is the most frequent type presenting aggressive and destructive characteristics with the involvement of posterior areas of jaws and impacted third molars in some cases [ 53 ]. Radiographically, MA shows as a radiolucent multilocular lesion with a ‘‘soap-bubbles” aspect associated with expansion and disruption of bone cortical [ 52 , 53 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The multicystic ameloblastoma (MA) is the most frequent type presenting aggressive and destructive characteristics with the involvement of posterior areas of jaws and impacted third molars in some cases [ 53 ]. Radiographically, MA shows as a radiolucent multilocular lesion with a ‘‘soap-bubbles” aspect associated with expansion and disruption of bone cortical [ 52 , 53 ]. A unicistic ameloblastoma (UA) is less aggressive and commonly mimics odontogenic cysts frequently related with teeth in the area, especially, mandible third molars.…”
Section: Literature Reviewmentioning
confidence: 99%